Where the Tiny Things Are: Feathered Essays - Walker, Nicole (punctum books, 2017)
In this collection of longer essays nested within brief, lyrical meditations, each piece focuses on some micro aspect of everyday life as a means of exploring complex macro systems-families, dinner parties, vineyards, deserts, nations. For example, Walker's own experience as the mother of a micropreemie (a baby born weighing less than one pound, twelve ounces, or before twenty-six weeks gestation), "the smallest thing in the world," spurs an exploration of, among other things, the economics of health care, the causes of premature births, and the ethics of extreme interventions. Where the Tiny Things Are is a book of ideas and an exploration of science. It is of the world and of the heart - both intensely personal and expansively empathetic.